2016
DOI: 10.7754/clin.lab.2016.151212
|View full text |Cite
|
Sign up to set email alerts
|

Human Epididymis Protein 4 (HE4) in Patients with Small-Cell Lung Cancer

Abstract: Diagnostic utility of HE4 was similar to that of NSE and ProGRP. Complementary to NSE, determination of HE4 seems to be helpful in evaluation of SCLC patients' prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A total of 492 items were identified (212 from PubMed, 262 from Embase, and 18 from the Cochrane library). After meticulous screening and inspection of the articles, finally, 18 articles were included in our final analysis [21,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Table 1 summarizes the characteristics of the included studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 492 items were identified (212 from PubMed, 262 from Embase, and 18 from the Cochrane library). After meticulous screening and inspection of the articles, finally, 18 articles were included in our final analysis [21,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Table 1 summarizes the characteristics of the included studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Our observation may be explained that all SCLC patients had bone metastases. Previous studies showed that HE4 is a potential marker for the diagnosis and follow up of NSCLC patients and could be helpful in evaluation of SCLC patient´s prognosis [43,44]. Celik and Bulut observed that HE4 is expressed in adenocarcinoma tissues but it is not frequent in SCLC [45].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study was conducted on SCLC using HE4 assays to analyze the serum of 63 patients with SCLC, compared to 66 controls (10). The AUC for HE4 was 0.884.…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity (43.8-69.4%) and specificity (78.5-95.0%) for lung cancer detection (6,7,8) has been previously identified and its increase in the serum after postoperative period was found to correlate with recurrence (9). Its serum concentration is also associated with tumor stage, and disease progression occurred within the first year in patients with small-cell lung cancer (SCLC) (10). Among locally advanced non-small cell lung cancer (NSCLC) patients, a higher serum level of HE4 has been found to predict non-responders to chemoradiotherapy (11).…”
Section: Introductionmentioning
confidence: 99%